Indole and p-cresol in feces of healthy subjects: Concentration, kinetics, and correlation with microbiome - Candeliere, Francesco; Simone, Marta; Leonardi, Alan; Rossi, Maddalena; Amaretti, Alberto; Raimondi, Stefano (Frontiers in Molecular Medicine, 2022)
Indole and p-cresol are precursors of the most important uremic toxins, generated from the fermentation of amino acids tryptophan and tyrosine by the proteolytic community of intestinal bacteria. The present study focused on the relationship between the microbiome composition, the fecal levels of indole and p-cresol, and their kinetics of generation/degradation in fecal cultures. The concentration of indole and p-cresol, the volatilome, the dry weight, and the amount of ammonium and carbohydrates were analyzed in the feces of 10 healthy adults. Indole and p-cresol widely differed among samples, laying in the range of 1.0–19.5 μg/g and 1.2–173.4 μg/g, respectively. Higher fecal levels of indole and p-cresol were associated with lower carbohydrates and higher ammonium levels, that are markers of a more pronounced intestinal proteolytic metabolism. Positive relationship was observed also with the dry/wet weight ratio, indicator of prolonged intestinal retention of feces. p-cresol and indole presented a statistically significant negative correlation with OTUs of uncultured Bacteroidetes and Firmicutes, the former belonging to Bacteroides and the latter to the families Butyricicoccaceae (genus Butyricicoccus), Monoglobaceae (genus Monoglobus), Lachnospiraceae (genera Faecalibacterium, Roseburia, and Eubacterium ventriosum group). The kinetics of formation and/or degradation of indole and p-cresol was investigated in fecal slurries, supplemented with the precursor amino acids tryptophan and tyrosine in strict anaerobiosis. The presence of the precursors bursted indole production but had a lower effect on the rate of p-cresol formation. On the other hand, supplementation with indole reduced the net rate of formation. The taxa that positively correlated with fecal levels of uremic toxins presented a positive correlation also with p-cresol generation rate in biotransformation experiments. Moreover other bacterial groups were positively correlated with generation rate of p-cresol and indole, further expanding the range of taxa associated to production of p-cresol (Bacteroides, Alistipes, Eubacterium xylanophylum, and Barnesiella) and indole (e.g., Bacteroides, Ruminococcus torques, Balutia, Dialister, Butyricicoccus). The information herein presented contributes to disclose the relationships between microbiota composition and the production of uremic toxins, that could provide the basis for probiotic intervention on the gut microbiota, aimed to prevent the onset, hamper the progression, and alleviate the impact of nephropaties.